2011
DOI: 10.1145/2010324.1964924
|View full text |Cite
|
Sign up to set email alerts
|

A programmable system for artistic volumetric lighting

Abstract: Figure 1: Our system was used to author artistic volumetric effects for the movie Tangled. Our technique's ability to produce curving light beams is used to match the organic artistic style of the film. AbstractWe present a method for generating art-directable volumetric effects, ranging from physically-accurate to non-physical results. Our system mimics the way experienced artists think about volumetric effects by using an intuitive lighting primitive, and decoupling the modeling and shading of this primitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…However, the proposed formulation could be adapted by ensuring that the editing function M x j ,x e is continuous and calculable for any point p e between p e and x e . Following an approach similar to light beams manipulation [13] could be envisioned to do such extension.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proposed formulation could be adapted by ensuring that the editing function M x j ,x e is continuous and calculable for any point p e between p e and x e . Following an approach similar to light beams manipulation [13] could be envisioned to do such extension.…”
Section: Discussionmentioning
confidence: 99%
“…Nowrouzezahrai et al . [NJS∗ 11] break down and edit the emissive properties of participating media. Our method also alters light propagation to isolate and render global shadows, but user control is deferred to post‐processing.…”
Section: Related Workmentioning
confidence: 99%
“…31,32 In computer graphics, striving for realism stimulated the development of illumination algorithms. [33][34][35][36] Studies in this field visualized light rays 37,38 avoiding clutter, 39 and showed various light properties. 30,40,41 Although the listed studies demonstrate a variety of light visualization methods, they are mostly targeted at the computer graphics audience and often take advantage of rendering methods.…”
Section: From Surfaces To Volumesmentioning
confidence: 99%